Protective effects of Salvia miltiorrhiza on adenine-induced chronic renal failure by regulating the metabolic profiling and modulating the NADPH oxidase/ROS/ERK and TGF-β/Smad signaling pathways. (15th February 2018) - Cai, Hongdie; Su, Shulan; Li, Yonghui; Zeng, Huiting; Zhu, Zhenhua; Guo, Jianming; Zhu, Yue; Guo, Sheng; Yu, Li; Qian, Dawei; Tang, Yuping; Duan, Jinao
Abstract: Ethnopharmacological relevance: Chronic renal failure (CRF) is defined as a progressive and irreversible loss of renal function and associated with inflammation and oxidative stress. Salvia miltiorrhiza (SM) is an important Chinese herb used in traditional Chinese medicine for treating cardiovascular diseases. The previous studies showed the SM exhibited significant protective effects on CRF. In this present study, the metabolic profiling changes and action mechanism of SM on CRF were explored. Aims of the study: The aims of this study were to illustrate the metabolic profiling changes of adenine induced CRF and analyze the protective effects and action mechanisms of SM ethanol extract (SMEE) and water extract (SMWE). Materials and methods: The animals were divided into normal group, CRF model group, Huangkui capsule-treated group, SMEE-treated group and SMWE-treated group. The UPLC−QTOFMS coupled with multivariate statistical methods were used to explore the changes of metabolic profile in plasma, urine and renal tissue from CRF rats simultaneously after treatment with SMEE and SMWE. Hematoxylin eosin (HE) staining and Masson staining were applied to observe pathological changes in renal tissue. Biochemical indicators including serum urea nitrogen (BUN), urine protein (UP) and serum creatinine (Scr) were measured according to the manufacturer's instructions of kits. Furthermore, HK-2 cell damaged model induced by ISF was established to access the protective effects and action mechanism. The dichlorodihydrofluorescein diacetate (DCFH-DA) assay was used to determine the reactive oxygen species (ROS) and Western blot was applied to analyze the expression of pathogenesis-related proteins in different groups. Results: The results showed that the ethanol extract (SMEE) and water extract (SMWE) of SM significantly inhibited the elevation of serum creatinine (Scr), blood urea nitrogen (BUN), urine protein (UP) and indoxyl sulfate (ISF) in adenine-induced CRF rats, especially SMEE exhibited more significant effects. Moreover, SM extracts obviously improved the symptoms of glomerular and tubular atrophy, focal calcium deposits, interstitial fibrosis, interstitial inflammation, and renal tissues. By metabolomics analysis, fifty-nine metabolites (thirteen in plasma, twenty-seven in urine and nineteen in kidney tissue) were up-regulated or down-regulated and contributed to CRF progress. After treatment of SM extracts, the altered metabolites were restored back to normal level. These potential biomarkers underpinning the metabolic pathways are including phenylalanine metabolism, pyrimidine metabolism, purine metabolism and tryptophan metabolism. Furthermore, SM extracts prevent epithelial-mesenchymal transition (EMT) of human renal tubular epithelial (HK-2) cell by inhibiting NADPH oxidase/ROS/ERK and TGF- β /Smad signaling pathways. Conclusions: SMEE and SMWE can significantly alleviate adenine-induced CRF via regulation of the metabolic profiling and modulation of NADPH oxidase/ROS/ERK and TGF-β/Smad signaling pathways, which provided important supports for the development of protective agent of SM for CRF. Graphical abstract: